The Remote Observatories of the Southeastern Association for Research in Astronomy (SARA). (30th November 2016) - Keel, William C.; Oswalt, Terry; Mack, Peter; Henson, Gary; Hillwig, Todd; Batcheldor, Daniel; Berrington, Robert; De Pree, Chris; Hartmann, Dieter; Leake, Martha; Licandro, Javier; Murphy, Brian; et al.
Abstract: We describe the remote facilities operated by the Southeastern Association for Research in Astronomy (SARA), a consortium of colleges and universities in the US partnered with Lowell Observatory, the Chilean National Telescope Allocation Committee, and the Instituto de Astrofísica de Canarias. SARA observatories comprise a 0.96 m telescope at Kitt Peak, Arizona; one of 0.6 m aperture on Cerro Tololo, Chile; and the 1 m Jacobus Kapteyn Telescope at the Roque de los Muchachos, La Palma, Spain. All are operated using standard VNC or Radmin protocols communicating with on-site PCs. Remote operation offers considerable flexibility in scheduling, allowing long-term observational cadences difficult to achieve with classical observing at remote facilities, as well as obvious travel savings. Multiple observers at different locations can share a telescope for training, educational use, or collaborative research programs. Each telescope has a CCD system for optical imaging, using thermoelectric cooling to avoid the need for frequent local service, and a second CCD for offset guiding. The Arizona and Chile telescopes also have fiber-fed echelle spectrographs. Switching between imaging and spectroscopy is very rapid, so a night can easily accommodate mixed observing modes. We present some sample observational programs. For the benefit of other groups organizing similar consortia, we describe the operating structure and principles of SARA, as well as some lessons learned from almost 20 years of remote operations.